2010
DOI: 10.1260/0144-5987.28.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Assisted Transesterification of Maize (Zea Mays L.) Oil as a Biodiesel Fuel

Abstract: Maize (Zea mays L.) oil is a highly valuable agricultural commodity for the Turkey. Transesterified maize oil has the global better properties because it has the greater monounsaturated content. Biodiesel has been prepared from maize by transesterification of the crude oil under microwave irradiation, with methanol to oil molar ratio of 10:1, in the presence of 1.5% NaOH as catalyst and 5 minutes time, the conversion of maize oil to methyl ester was over 98%. Compared with conventional heating methods, the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Microwave assisted extraction and transesterification was performed using various types of feedstock ranging from edible oils to non-edible and waste frying oils. The experimental studies are summarized in Table 2 [64,106,111,118,[120][121][122][123][124][125]127,130,[132][133][134][135][136][137][138][139][141][142][143][144][145][146][147][148][149][150][151][152][153][154][155].…”
Section: Microwave-enhanced Transesterificationmentioning
confidence: 99%
“…Microwave assisted extraction and transesterification was performed using various types of feedstock ranging from edible oils to non-edible and waste frying oils. The experimental studies are summarized in Table 2 [64,106,111,118,[120][121][122][123][124][125]127,130,[132][133][134][135][136][137][138][139][141][142][143][144][145][146][147][148][149][150][151][152][153][154][155].…”
Section: Microwave-enhanced Transesterificationmentioning
confidence: 99%
“…In Azcan and Danisman's work (2007), microwave heating effectively reduced reaction time from 30 min (for a conventional heating system) to 7 min. Ozturk et al (2010) studied microwave assisted transesterification of maize oil, using a molar ratio alcohol/maize-oil of 10:1, and 1.5% w/w NaOH as catalyst. A 98.3% conversion rate is obtained using methanol for 5 min.…”
Section: Microwave Technologymentioning
confidence: 99%
“…From equation (18), the plot of Àln 1 À X A ð Þvs t are drawn for different reaction scenarios and were compared with first order reaction line, and the corresponding correlation coefficients were found to be 0.9346, 0.9439 and 0.932 for 70, 60 and 50°C reaction respectively while keeping other reaction parameters same at ethanol/oil molar ratio of 9:1, 600 rpm and 3 wt % catalyst. While comparing with second order reaction, the correlation coefficient was found to be 0.634 (Fig.…”
Section: Experimental Approachmentioning
confidence: 99%
“…Hence there has been a growing impetus on the heterogeneous synthesis, identifying novel and effective catalysts and cost effective feedstock as the main hurdle in the commercialization of biodiesel production by transesterification reaction has been the high cost of raw materials which contributes to 70 % of total cost [9]. Various research studies have been reported on this topic like process standardization with reference to various critical parameters like nature of vegetable oil and alcohol, reactant mole ratio, nature and amount of catalyst, reaction time, agitation rate and temperature and employing different reaction conditions like microwave irradiation, ultrasonic assisted and supercritical conditions to maximize biodiesel yield and reaction rate [10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%